OXYGEN SATURATION AND POSTPARTUM OUTCOMES IN MOTHERS WITH CONGENITAL HEART DISEASE: A CROSS-SECTIONAL STUDY AT RSSA, MALANG - Cahyaningtyas, Rara Arisya; Swastika Putri , Valerinna Yogibuana; Agung Indrawan, I Wayan (Journal of Community Health and Preventive Medicine, 2026)
Congenital Heart Disease (CHD) is a structural abnormality of the heart, such as abnormalities in the heart valves, failure to close the embryological hole in the heart, and other forms of congenital heart defects. Pregnancy with CHD requires special intervention from a multidisciplinary team. This is because pregnancy with CHD can cause many complications and increase the risk of maternal and neonatal death. Maternal oxygen saturation greatly affects the development of the fetus she is carrying and has an impact on maternal complications after delivery. To discuss the relationship between oxygen saturation and maternal complications after delivery and neonatal complications in Saiful Anwar General Hospital. This analytical observational study uses a comparative chi-square test and a multivariate logistic regression test conducted on 25 maternal and 21 neonatal data. The research data came from medical records at Saiful Anwar General Hospital, Malang. The study's results showed no significant relationship between maternal oxygen saturation and maternal complications (p-value>0.05). Meanwhile, the relationship between maternal oxygen saturation and neonatal clinical outcomes showed significant results in the variable of body weight (p-value=0.001, RR=7.50), but other variables were not significant (p-value> 0.05). The multivariate logistic regression test results showed that the parameters possibly related to maternal complications were primigravida (p-value>0.05). This study concludes that maternal oxygen saturation is unrelated to maternal complications after delivery, and neonatal clinical outcomes are only significantly related to the body weight variable.